Apolipoprotein E ε4 allele is not associated with elite rugby status but is present in 30% of athletes - Shane Heffernan (23rd European Congress of Sports Science, 2018)
The APOE ε4 allele is a candidate genetic marker for risk and severity of mild traumatic brain injury (mTBI) including sport-related concussion. ε4 allele carriers experience reduced motor rehabilitation outcomes, poorer neurocognitive outcomes, increased cognitive impairments, amnesia and memory defects following mTBI. Concussion injury (mTBI) rates in elite rugby players are substantial and, consequently, elevated risk and severity of mTBI due to carriage of the ε4 risk allele may be detrimental to both the short-term and long-term health of elite players and reduce their likelihood of career success. Therefore, we investigated APOE ε2/ε3/ε4 of athletes at the elite level of competitive rugby. METHODS: Genomic DNA was collected from 1006 Caucasian participants, comprising 523 elite rugby athletes and 483 non-athlete controls (RugbyGene study). All samples were genotyped for the APOE ε2/ε3/ε4 variants (rs429358 and rs7412) using real-time PCR. Pearson’s Chi-square (χ2) tests were used to compare genotype frequencies between groups. RESULTS: No genotype differences (P > 0.05) were identified between controls (ε4/ε4 = 2.3%) and either rugby union (ε4/ε4 = 3.7%) or rugby league (ε4/ε4 = 1.3%) athletes. Similarly, when the presence of the ε4 allele (ε4+) was compared to non-carriers, no allelic differences were observed between controls (ε4+ = 28%) and either rugby union (ε4+ = 29%) or rugby league (ε4+ = 33%). Rugby union athletes with international competitive experience showed an underrepresentation of the ε4/ε4 genotype compared to those without international experience (2.6% versus 4.7%, P = 0.01), but exhibited a similar frequency to controls (2.3%). CONCLUSION: These results suggest that APOE ε4 plays little or no role in the likelihood of a rugby athlete achieving elite competitive status. However, our data suggest that ~30% of rugby athletes could be at greater risk of poor recovery from concussion due to carriage of the ε4 APOE allele and this warrants research to establish if previously identified APOE ε4-mTBI associated outcomes exist in elite rugby.